2019
DOI: 10.1111/jphs.12293
|View full text |Cite
|
Sign up to set email alerts
|

Parental views and attitudes towards use of unlicensed and off‐label medicines in children and paediatric clinical trials: an online cross‐sectional study in the Arab world

Abstract: Objectives The present study aimed to explore views and attitudes of parents towards the use of unlicensed and off-label medicines in children, paediatric clinical trials, and the role of pharmacists in the safety and effectiveness of medicines. Methods A cross-sectional electronic survey was conducted over social media networks in the Arab world to assess parents' views and attitude towards use of unlicensed/offlabel medicines and clinical trials in children. Validated questionnaire was adopted to achieve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…While nurses in Jordan cannot legally write prescriptions, they do contribute significantly to antibiotic management and play a critical part in the antibiotic distribution process. Given their pivotal role [9,21,22]. The results showed that Jordanian nursing staff appears not knowledgeable of the causes of ABR among children, which include improper prescription, prolonged antibiotic treatment, and self-medication [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While nurses in Jordan cannot legally write prescriptions, they do contribute significantly to antibiotic management and play a critical part in the antibiotic distribution process. Given their pivotal role [9,21,22]. The results showed that Jordanian nursing staff appears not knowledgeable of the causes of ABR among children, which include improper prescription, prolonged antibiotic treatment, and self-medication [16].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance (ABR), especially in Jordan, is a worldwide health crisis, and one of the leading reasons for this crisis is the improper use of antibiotics [1]. The increased frequency of infectious illnesses is threatening to the improper use of antibiotics within children [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Studying the public views towards medicine use is an important matter, as people's insight towards treatment and medication has its effect on medication adherence . When parents administer medicine to their children, it is critical to believe that the administered medicine is effective and that the child is in real need for the medicine .…”
Section: Discussionmentioning
confidence: 99%
“…50,51 The resulting increased involvement of patients in their care had to be achieved by maintaining the balance of providing additional information about unlicensed "special" medicines without causing concern. Participants gave examples of concerns raised by patients consistent with that in the literature, showing increased concern once fully informed about the use of unlicensed medicines, 19,52,53 one participant explained how parents often questioned the need for the unlicensed medicine prescribed for their child, suggesting that the concerns and perceptions highlighted may lead to non-adherent behaviours. 54,55 Literature reports the successful use of a range of educational interventions to increase patient awareness on medication use for different conditions.…”
mentioning
confidence: 89%